EXPLORING STUDENTS’ PURPOSES FOR READING BOOK - Radiatan Mardiah; Melati (Universitas Jambi, 2021)
Stating a purpose for reading may help shaping the way the students read. It could save time and improve understanding. This qualitative study explored the university students’ purpose for reading book. The participants were a class of law faculty students learning English as a general purpose in a state university in Jambi. The main source of data was the document in the form of students’ reading report. The document was analyzed using qualitative approach. To clarify the data gained, semi-structured interview was applied. It is revealed that students’ purposes for reading book was for content and they use low order thinking verb such as to know to realize it. For more comprehensive book reading, it is suggested that the students use different verbs such as to interpret, to classify, or to explore for stating their purposes.